The teaching methodological and pedagogic practice analysis for teaching english as FL/L3 for deaf students - CARDOSO, Kimberly Marjórie dos Santos (2023)
The present study deals with the analysis of the methodological and pedagogical practice of a teacher from the public-school system in which two deaf students are present in her classroom. Thus, the following specific objectives were outlined for this research: To observe the existence or not of specific material of English language teaching for the deaf people provided by the educational institution or by the teacher; Verify deaf students participation and interaction’ during English language classes; Investigate if there are didactic inclusive adaptations of English classes by the teacher. This research was conducted through survey study sustained by the bibliographic research. The instruments used in data generation for this research were: non participating observation in English language classes and semi-structured interview with the teacher. This qualitative research was carried out at a public school, that is, an inclusive mainstream school in the Altamira-Pará city, in the Brazil’s north. The results showed that both the teacher and the institution are aware of the responsibility in offering an inclusive and meaningful teaching for deaf students enrolled at the researched school. It is necessary, though, improve the pedagogical practices of the professionals involved in the teaching and learning of English as L3 / LE for deaf students through a continuing training.